Do Early Childhood Schools Have Contextual Effect on Child Development Aged 3-6 Years in Tanjung Jabung Timur, Jambi? - Hardilla, Dinda Septiani; Salimo, Harsono; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background:  Early childhood development is a critical period in children's lives. The development index in early childhood in Indonesia is relatively low compared to other developing countries, which is 88.3%. Various factors that can influence early childhood development were the nutritional status of children, stimulation by parents, exclusive breastfeeding, dietary patterns, and parental characteristics. This study aimed to analyze the contextual influence of early childhood education on child development in Tanjung Jabung Timur, Jambi.Subjects and Method: This was a cross sectional study conducted at 25 early childhood schools in Tanjung Jabung Timur, Jambi, from September to October 2019. A sample of 200 children aged 3-6 years old was selected by stratified random sampling. The dependent variable was child development. The independent variables were nutritional status, dietary pattern, exclusive breastfeeding, maternal education, maternal occupation, and family income. Child development was measured by The Indonesian child development prescreening questionnaire. The other data were collected by questionnaire. The data were analyzed by a multilevel multiple logistic regression run on Stata 13.Results: Early childhood development increased with good nutritional status (b= 1.88; 95% CI= 0.48 to 3.28; p= 0.008), good dietary pattern (b= 1.58; 95% CI= 0.26 to 2.91; p= 0.019), exclusive breastfeeding (b= 0.64; 95% CI= -0.69 to 1.99; p= 0.346), maternal education ≥High school (b=  2.45; 95% CI= 0.97 to 3.92; p= 0.001), and family income ≥Rp 2,840,000 (b= 1.93; 95% CI= 0.32 to 0.53; p= 0.018). Early childhood development decreased with maternal working outside the house (b= -1.42; 95% CI= -2.66 to -0.17; p= 0.025). Early childhood school had low effect on child development with intra-class correlation= 10.09%.Conclusion: Early childhood development was influenced by nutritional status, dietary patterns, exclusive breastfeeding, maternal education, maternal employment, and family income. Early childhood education has contextual influence on child development.Keywords: child development, early childhood educationCorrespondence: Dinda Septiani Hardilla. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java. Email: dindaseptianihardilla15@gmail.com. Mobile: 082373568987.Journal of Maternal and Child Health (2020), 5(2): 120-128https://doi.org/10.26911/thejmch.2020.05.02.01